Islamic Educational Values in the Debus Manaqib Tradition of Kwamor - Mustafa Mahu; Muhammad Rizal Toyo (IAIN Ambon, 2023)
This study analyzes Islamic educational values in the Debus tradition associated with Shaykh Abdul Qadir al-Jilani in Kwamor, East Seram. Locally called Debus, the documented practice is substantively closer to communal manaqib reading than to the martial-ritual performance commonly identified as debus in Indonesian cultural studies. The study employs historical research combined with pedagogical content analysis. Data were drawn from the original description of the Kwamor tradition and recent scholarly works on manaqib, Islamic character education, value internalization, and local wisdom-based Islamic religious education. Source criticism, thematic coding, interpretation, and historiographical writing were used to distinguish historical information, community beliefs, and educational meanings. The findings show that the tradition contains potential values of tawhid, worship discipline, piety, humility, patience, self-control, respect for scholars, solidarity, mutual assistance, responsibility, cultural literacy, and religious moderation. These values are transmitted through exemplary narratives, repeated prayer and remembrance, moral advice, intergenerational participation, and communal religious culture. The tradition can therefore be positioned as a form of nonformal Islamic religious education and a contextual learning resource. Its pedagogical use, however, requires normative clarification based on the Qur'an and Sunnah, critical literacy regarding hagiographic narratives, and reflective activities that connect ritual participation with observable moral conduct.